Enhancer-Binding Proteins HrpR and HrpS Interact To Regulate hrp-Encoded Type III Protein Secretion in Pseudomonas syringae Strains - Hutcheson, Steven W. (American Society for Microbiology, 2001)
In Pseudomonas syringae strains, the hrp-hrc pathogenicity island consists of an HrpL-dependent regulon that encodes a type III protein translocation complex and translocated effector proteins required for pathogenesis. HrpR and HrpS function as positive regulatory factors for the hrpL promoter, but their mechanism of action has not been established. Both HrpR and HrpS are structurally related to enhancer-binding proteins, but they lack receiver domains and do not appear to require a cognate protein kinase for activity. hrpR and hrpS were shown to be expressed as an operon: a promoter was identified 5′ to hrpR, and reverse transcriptase PCR detected the presence of an hrpRS transcript. The hrpR promoter and coding sequence were conserved among P. syringae strains. The coding sequences for hrpR and hrpS were cloned into compatible expression vectors, and their activities were monitored in Escherichia coli transformants carrying an hrpL′-lacZ fusion. HrpS could function as a weak activator of the hrpL promoter, but the activity was only 2.5% of the activity detected when both HrpR and HrpS were expressed in the reporter strain. This finding is consistent with a requirement for both HrpR and HrpS in the activation of the hrpL promoter. By using a yeast two-hybrid assay, an interaction between HrpR and HrpS was detected, suggestive of the formation of a heteromeric complex. Physical interaction of HrpR and HrpS was confirmed by column-binding experiments. The results show that HrpR and HrpS physically interact to regulate the ς(54)-dependent hrpL promoter in P. syringae strains.